Review article: the investigation and management of rectal neuroendocrine tumours. Issue 4 (15th June 2016) - Basuroy, R.; Haji, A.; Ramage, J. K.; Quaglia, A.; Srirajaskanthan, R.
Summary: Background: Rectal neuroendocrine tumours (NETs) are increasingly identified at endoscopy possibly as a result of bowel cancer screening programmes. Aim: To present a review of the literature to aid clinicians in the diagnosis and management of rectal neuroendocrine tumours. Methods: A literature search was conducted through MEDLINE using search terms: rectal, rectum, carcinoid, NET, therapy, endoscopy, mucosal resection, submucosal dissection. Relevant articles were identified through manual review with reference lists reviewed for additional articles. Results: The incidence of rectal neuroendocrine tumours is approximately 1 per 100 000 population per year with the majority (80–90%) being <1 cm and localised to the submucosa. Metastatic disease is infrequent (<20%) with risk factors including size, atypical appearance, grade and depth of invasion. The primary resection modality influences complete resection rates and the need for secondary therapy. A thorough pre‐resection diagnostic work up is required for lesions that are at higher risk of invasion and metastasis. Device‐assisted endoscopic mucosal resection and endoscopic submucosal dissection are used to resect localised rectal neuroendocrine tumours <2 cm. Transanal surgery is also used to resect localised 1–2 cm rectal neuroendocrine tumours. Oncological surgical resection is used for rectal neuroendocrine tumours that are >2 cm or with invasion and regional disease. The treatment of advanced disease is multimodal. Conclusions: The long‐term tumour biology of small rectal neuroendocrine tumours remains unclear. There is uncertain impact from bowel cancer screening programmes on rectal neuroendocrine tumour incidence, morbidity and mortality. Referral to neuroendocrine tumour centres for patients with locally advanced disease or metastatic disease is recommended.